2012
DOI: 10.3109/02770903.2012.669442
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Analysis of Candidate Genes Involved in Neurogenic Inflammation in Pediatric Asthma and Related Phenotypes: A Case–Control Study

Abstract: Our results suggest that genetic variants of MAP3K1 and NGF genes involved in the regulation of neurogenic inflammation may contribute to asthma, possibly via enhanced NGF expression and MAPK signaling pathway activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
0
11
0
3
Order By: Relevance
“…In that study, the BDNF SNP rs7124442 correlated with increased levels of exhaled nitric oxide, but was not associated with asthma susceptibility. However, other results from that study confirmed that neurogenic inflammation contributed to bronchial asthma . Another important study from Germany investigated whether polymorphisms in the BDNF gene influenced the development or severity of asthma and other atopic diseases.…”
Section: Discussionmentioning
confidence: 75%
“…In that study, the BDNF SNP rs7124442 correlated with increased levels of exhaled nitric oxide, but was not associated with asthma susceptibility. However, other results from that study confirmed that neurogenic inflammation contributed to bronchial asthma . Another important study from Germany investigated whether polymorphisms in the BDNF gene influenced the development or severity of asthma and other atopic diseases.…”
Section: Discussionmentioning
confidence: 75%
“…При сопоставлении генотипа и фенотипа при одной из идентифицированных миссенс-мутаций было установлено, что у всех пациентов с этой мутацией отмечался мужской фенотип с гипоспадией. Данная миссенс-мутация также ассоциирована с бронхиальной астмой [12]; аномалии развития наружных гениталий ранее не были описаны. Таким образом, ее значимость о стается неизвестной.…”
Section: Discussionunclassified
“…Наружные половые органы были сформированы неправильно [клитор гипертрофирован (2,5-3 см) с головкой, слабо развитые кавернозные тела, меатус у основания клитора, скротолабиальный шов расщеплен, вход во влагалище сужен]. Отмечались высокий уровень гонадотропинов [ЛГ 88 Ед/л (2,(6)(7)(8)(9)(10)(11)(12), ФСГ 104 Ед/л (1,(9)(10)(11)7)], эстрадиола [70 пмоль/л (97-592)], тестостерона [3,11 нмоль/л (0,1-2,7)]. Показатели дигидроэпиандростендиона-сульфата (ДГЭА-С) и 17-гидроксипрогестерона (17-ОНП) находились в пределах референсных значений [7,52 мкмоль/л (0,92-7,6) и 3,6 нмоль/л (0,1-7,0) соответственно].…”
unclassified
“…The significant association of this mutation have been shown to be associated with asthma. [10] However, genital abnormality with this polymorphism has not been reported.…”
Section: Discussionmentioning
confidence: 99%